Composition and «pointless» painting in system of nonconventional approaches to creative process (Pedagogy of Higher and Secondary Education, 2022)
In article the points of view on «pointless» painting as on one of aspects of abstract art and nonconventional approaches to creative process are analysed.
Keywords: «pointless» painting; metaphor; allegory; semantic link; composition